Efficiency of CNT-based rotation transmission nanosystem in water. (23rd March 2021) - Shi, Jiao; Wu, Puwei; Li, Xin; Cai, Kun; Zhang, Yingyan
Abstract: Carbon nanotubes (CNTs) have been widely used as the motor and rotor in a rotational transmission nanosystem (RTnS), whose function is to transfer the input rotational frequency of the motor into the output frequency of the rotor through motor-rotor interactions. A wide range of techniques has been explored to achieve a CNT-based RTnS with a stable and adjustable transmission. In this work, a CNT-based rotor is partly immersed into a water box and the associated water-rotor interaction leads to effective manipulation of the transmission efficiency of RTnS. Molecular dynamics simulations are performed on this new RTnS to investigate the dynamic response of the rotor and the local flow field near the water-rotor interface. Various parameters, including ambient temperature, tubes' radii, and volume fractions of water in the box ( V f ) are examined for their effects on the rotational transmission efficiency. This study offers useful guidelines for the design of stable RTnS with controllable transmission efficiency.